Perennial Peanut: Forage Nutritional Composition and Feeding Value - Bob Myer; Lori Warren; Juliet Eckert; Dennis Hancock; Ann Blount; Clay Olson (EDIS)
AN234, a 6-page fact sheet by Bob Myer, Lori Warren, Juliet Eckert, Dennis Hancock, Ann Blount, and Clay Olson, summarizes nutritional composition data and results of animal feeding studies, including studies with horses. Includes references. Published by the UF Department of Animal Sciences, February 2010.